Proppant distribution characteristics based on the coring well analysis - Wang, Tao; Zhang, Jizhuo; Xiang, Yuankai; Tang, Wei; Yin, Shitan; Ye, Yiping; Shi, Shanzhi; Li, Yi (Frontiers in Energy Research, 2024)
It is significant to clarify the proppant distribution pattern under real fracturing conditions to optimize the sand addition process in hydraulic fracturing of the Mahu tight conglomerate reservoir. However, the laboratory experiment is far from the real fracturing condition due to the limitations of scale, pumping scale, and stress conditions. In this paper, the proppant in cuttings and mud was obtained by screening and cleaning samples from the high-deviated coring well of the Mahu conglomerate reservoir in Xinjiang. The sphericity of particles was observed by a continuous variable magnification microscope, and the transparency (TR) of particles and the red-blue difference (RBD) of reflected light were followed by transmitted light. Considering these three factors, the proppant identification method in cuttings was established to obtain the spatial location and distribution of proppant along the whole well section. The effect of proppant transport and placement was evaluated. The results show that: (1) Compared with the formation of mineral particles, the proppant has better sphericity, TR>20%, and RBD > 30. Combined with the surface roughness, luster, and associated minerals, the particle can be evaluated as a proppant. (2) The content of proppant with small particle size (40/70 mesh) is significantly higher than that with large particle size (20/40 mesh), which ranges from 10‰ to 450‰ and 5‰ to 280‰, respectively. (3) Horizontally, 20/40 mesh proppant migrates approximately 10m, and 40/70 mesh proppant migrates approximately 23 m in the hydraulic fracture. (4) In the longitudinal fracture, 20/40 mesh proppant was concentrated at a 12 m vertical distance from the adjacent well, while 40/70 mesh proppant was placed at a larger longitudinal range, approximately 10 m above and 10 m below the adjacent well. The research results have certain reference significance for the improvement measures of the sand-adding process in the Mahu tight conglomerate reservoir.